2011
DOI: 10.4172/2155-9546.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Efficient Utilization of Antibiotics for the Development of a Stable Transformation System in Porphyra yezoensis (Bangiales, Rhodophyta)

Abstract: Despite the development of transient gene expression in red algae Porphyra species, a stable transformation system has not been established in these algae yet. One reason for the difficulty in the transformation is the lack of a way to select transformed cells from the algae. Thus, to identify antibiotics suitable for the selection of stably transformed cells, we tested the gametophyte for sensitivity to 6 antibiotics, ampicillin (Am), kanamycin (Km), hygromycin (Hm), geneticin (G418), chloramphenicol (Cm) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Therefore, the next step is to develop the gene targeting system via integration of a foreign gene into the genome and the system for selection of transformed cells. Since candidates of antibiotic agents for selection of transformed algal cells were mentioned recently [101][102][103]106], it is necessary to confirm the possibility of stable integration of a plasmid or a DNA fragment containing the selection maker gene into the seaweed genome. Once a positive result is obtained, it could lead us to establish the gene targeting method via the homologous recombination using an appropriate antibiotics resistance gene, if possible, with the heterologous promoter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the next step is to develop the gene targeting system via integration of a foreign gene into the genome and the system for selection of transformed cells. Since candidates of antibiotic agents for selection of transformed algal cells were mentioned recently [101][102][103]106], it is necessary to confirm the possibility of stable integration of a plasmid or a DNA fragment containing the selection maker gene into the seaweed genome. Once a positive result is obtained, it could lead us to establish the gene targeting method via the homologous recombination using an appropriate antibiotics resistance gene, if possible, with the heterologous promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the sensitivity of P. yezoensis gametophytes to ampicillin, kanamycin, hygromycin, geneticin (G418), chloramphenicol and paromomycin was investigated, and lethal effects of these antibiotics on gametophytes were observed at more than 2.0 mg mL -1 of hygromycin, chloramphenicol and paromomycin and 1.0 mg mL -1 of G418, whereas P. yezoensis gametophytes were highly resistant to ampicillin and kanamycin [101]. Although these concentrations are in fact very high in comparison with the cases for the red alga Griffithsia japonica and the green alga C. reinhardtii that were highly sensitive to 50 μg mL -1 and 1.0 μg mL -1 of hygromycin [96,102], these four antibiotics and corresponding resistance genes are suitable for the selection of genetically transformed cells from P. yezoensis gametophytes.…”
Section: Towards Genetic Transformation In Red Seaweedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings above indicate that using antibiotics will be pragmatic. Doses of 2.0 mg/ml hygromycin, chloramphenicol, or paromomycin, or of 1.0 mg/ml G418, were lethal to P. yezoensis gametophytes, although these gametophytes were also highly resistant to ampicillin and kanamycin (Takahashi et al, 2011 ). Thus, as mentioned in Mikami ( 2013 ), these four antibiotics and their corresponding resistance genes are thought to be suitable for the selection of genetically transformed cells from P. yezoensis gametophytes.…”
Section: Selection Of Genetically Transformed Cellsmentioning
confidence: 99%
“…Recently, we have revealed that P. yezoensis cells are sensitive to several aminoglycoside antibiotics, including hygromycin B, paromomycin, and geneticin (Takahashi et al 2011). Thus, these antibiotics are possible candidate selection agents for stable P. yezoensis transformation.…”
Section: Introductionmentioning
confidence: 99%